Catalase blockade reduces the pressor response to central cholinergic activation - Lauar, Mariana R. [UNESP]; Colombari, Débora S.A. [UNESP]; Colombari, Eduardo [UNESP]; De Paula, Patrícia M. [UNESP]; De Luca, Laurival A. [UNESP]; Menani, José V. [UNESP] (Elsevier, 2019)
Intracerebroventricular (icv) injection of hydrogen peroxide (H2O2), a reactive oxygen species, or the blockade of catalase (enzyme that degrades H2O2 into H2O and O2) with icv injection of 3-amino-1,2,4-triazole (ATZ) reduces the pressor effects of angiotensin II also injected icv. In the present study, we investigated the effects of ATZ injected icv or intravenously (iv) on the pressor responses induced by icv injections of the cholinergic agonist carbachol, which similar to angiotensin II induces pressor responses that depend on sympathoexcitation and vasopressin release. In addition, the effects of H2O2 icv on the pressor responses to icv carbachol were also tested to compare with the effects of ATZ. Normotensive non-anesthetized male Holtzman rats (280–300 g, n = 8–9/group) with stainless steel cannulas implanted in the lateral ventricle were used. Previous injection of ATZ (5 nmol/1 μl) or H2O2 (5 μmol/1 μl) icv similarly reduced the pressor responses induced by carbachol (4 nmol/1 μl) injected icv (13 ± 4 and 12 ± 4 mmHg, respectively, vs. vehicle + carbachol: 30 ± 5 mmHg). ATZ (3.6 mmol/kg of body weight) injected iv also reduced icv carbachol-induced pressor responses (21 ± 2 mmHg). ATZ icv or iv and H2O2 icv injected alone produced no effect on baseline arterial pressure. The treatments also produced no significant change of heart rate. The results show that ATZ icv or iv reduced the pressor responses to icv carbachol, suggesting that endogenous H2O2 acting centrally inhibits the pressor mechanisms (sympathoactivation and/or vasopressin release) activated by central cholinergic stimulation.
Keywords: Blood pressure; Catalase inhibitor; Cholinergic activation; H2O2; Hypertension; Reactive oxygen species